LEARNING VOCABULARY THROUGH COLOURFUL PUZZLE GAME - Risca Dwiaryanti (OKARA: Jurnal Bahasa dan Sastra, 2014)
Vocabulary plays an important role because it links to the four skills of listening, speaking, reading, and writing. Those aspects should be integrated in teaching and learning process of English. However, the students must be able to know the meaning of each word or vocabulary of English in order to master the four skills. It is as a mean to create a sentence in daily communication to show someone’s feeling, opinion, idea, desire, etc. So that, both speakers understand what the other speaker mean. However, English as a second language in Indonesia seems very hard for the students to master vocabulary of English. It makes them not easy to be understood directly and speak fluently. The students, sometimes, get difficulties in understanding, memorizing the meaning of the vocabulary, and getting confused in using the new words. There must be an effective strategy to attract students’ interest, break the boredom, and make the class more lively. Based on the writer experience, Colourful Puzzle Game is able to make the students learn vocabulary quickly. It needs teacher’s creativity to create the materials of this game based on the class condition. The teacher just need a game board made from colourful papers, write any command and prohibition words on it. A dice is a tool to decide where the player should stop based on the number. Some pins as counter as sign of each player.